Real-world in-hospital outcomes and potential predictors of heart failure in primigravid women with heart disease in Southwestern China - Wuwan Wang; Lu Wang; Panpan Feng; Xiyao Liu; Rui Xiang; Li Wen; Wei Huang (BMC, 2020)
Abstract Background Little is known about the status of maternal, obstetric, and neonatal complications and the potential predictors of developing heart failure (HF) in mothers with underlying heart disease (HD) in Southwestern China. Methods The eligible records from the YiduCloud database from December 1, 2010 to December 31, 2019 were screened. The maternal clinical characteristics and the in-hospital outcomes were collected and compared in primigravid women with and without HD. The HD subtypes analyzed included valvular HD (VHD), cardiomyopathy, adult congenital HD (ACHD), pulmonary hypertension (PH), and other cardiac conditions. Results Among 45,067 primigravid women, 508 (1.1%) had HD, in which 207 (41%) had ACHD, 66 (13%) had VHD, 84 (17%) had cardiomyopathy, 7 (1%) had PH, and 144 (28%) had other cardiac diseases. The maternal cardiac events and the neonatal complications occurred in 28% and 23.3%, respectively, of women with HD and were predominant in the PH group. In multivariable regression, HF was associated with the New York Heart Association (NYHA) class ≥3 (OR = 15.9, 95% confidence interval [CI] = 2.5-99.7; P = 0.003), heart rate ≥ 100 bpm (OR = 3.8, 95% CI = 1.1-13.5; P = 0.036), ejection fraction ≤60% (OR = 6.4, 95% CI = 2.0-21.0; P = 0.002) and left ventricular end-diastolic diameter ≥ 50 mm (OR = 3.4, 95% CI = 1.1-11.2; P = 0.041) at the beginning of pregnancy. Conclusions Maternal and neonatal complications are higher in primigravid women with HD particularly in the PH group compared with primigravid women without HD. Women with HD should be guided on the potential predictors for HF and closely monitored during pregnancy to reduce maternal and neonatal complications.